Treatment of malaria (lecture) - A. F. Popov (Журнал инфектологии, 2014)
The article presents the current strategy of malaria treating. Unlike previous years, the new treatment is supplemented with artemisinin-based combination therapy – ACT, where two or more anti-malarial drug have multidirectional mechanism of action on P. falciparum. Previously recommended quinine related to alternative antimalarial agents and it is recommended only in case of absence or inability of artesunate (or artemether) using. At the same time, tropical malaria infection during the first trimester is treated by quinine in combination with clindamycin for 7 days. In the second and third trimester artesunate with clindamycin are usually appointed. Pathogenetic and symptomatic features of treatment of severe malaria are observed.